REASONS FOR INSUFFICIENT INNOVATION IN THE POLISH ECONOMY - Bal-Wozniak, Teresa (Journal of European Economy, 2017)
In spite of the innovation’s permanent place in economics, it deserves a new look. Consequently, the level of innovativeness is the responsibility of the individual, the economic agent. The aim of the paper is to reflect on searches for answers to numerous questions touching on how? How can influence be exerted on individual’s level of innovativeness without being in conflict with natural processes to which he as a subject is subordinated? How can we arrive at such a situation where everyone, irrespective of position held or social and professional role played, would want, know and be able to undertake effective realization of innovative activity, taking advantage of the knowledge he possesses for beneficial purposes. How to achieve a given level of management of the individual’s innovativeness, which would guarantee an increase in corporate innovativeness, including the economy as a whole? How to merge marketing mechanisms with the facilitating role of the state in innovation management, so that they could satisfy demands of the globalizing economy that is based on knowledge and human capital?